Representaciones sociales de ser egresadas de la carrera de enfermería de la Universidad Nacional De Trujillo - Tolentino Valera, Katty Elizabeth (2015)
This qualitative research approach and method of social representations, which was conducted in order to determine the social representation of being graduates of the undergraduate course at the National University of Trujillo. Participants were twenty four 24 graduates nurses from the National University of Trujillo who work in institutions of the Ministry of Health, EsSalud and Network Trujillo for data collection using semi-structured interviews and which were processed by the method of content partnerships, emerging three categories: (1) Satisfaction and Pride; (2) Prestige and Opportunities; (3) Training enough and competent. Referrals are to be satisfied and proud graduates of the nursing career at the National University of Trujillo, as well as the roles within their workplace also be manifested graduates of the Nursing National University Trujillo gives greater opportunities both in the workplace and in the different areas plays and this is also due to the prestige available to college graduates finally indicate that the received wisdom are the basics and you should always be in constant updating of knowledge.